2012
DOI: 10.1136/bmjopen-2012-001413
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of the association of hypnotic use with mortality in postmenopausal women

Abstract: ObjectivePrevious studies found an association between hypnotic use and mortality risk. The prospective outcome data and the many baseline risk factors included in the Women's Health Initiative (WHI) provide an opportunity to better understand the reasons for this association.SettingThe WHI is a long-term national health study that focused on strategies for preventing disease in postmenopausal women. Participants were enrolled from 1993 to 1998.DesignBaseline hypnotic use was evaluated for an association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…Short-term hypnotic use is unsafe Data provided by Palmaro et al 16 and Chung et al 17 expanded the hints in the other large epidemiologic studies 18-20 that short-term hypnotic usage has surprisingly high risks: apparently short-term hypnotic use has higher risks than long-term usage on a per dose or per-unit-time basis. It is logical that for a patient with an "overdose" of common contributory factors such as aging, obesity, sleep apnea, alcohol overuse, and opiate use, even a single hypnotic dose could be lethal on the first night of consumption.…”
Section: Results Had Many Similarities To Those Of Weich Et Almentioning
confidence: 94%
See 3 more Smart Citations
“…Short-term hypnotic use is unsafe Data provided by Palmaro et al 16 and Chung et al 17 expanded the hints in the other large epidemiologic studies 18-20 that short-term hypnotic usage has surprisingly high risks: apparently short-term hypnotic use has higher risks than long-term usage on a per dose or per-unit-time basis. It is logical that for a patient with an "overdose" of common contributory factors such as aging, obesity, sleep apnea, alcohol overuse, and opiate use, even a single hypnotic dose could be lethal on the first night of consumption.…”
Section: Results Had Many Similarities To Those Of Weich Et Almentioning
confidence: 94%
“…It should be noted that Weich et al 19 and Palmaro et al 16 found significant hazard ratios associated with diazepam and other benzodiazepines that are not considered hypnotics (though tranquilizer benzodiazepines may often be used for sleep). These more modern data with better drug identification and measurements of prescriptions during follow-up must be considered more reliable, but neither "Valium" nor "Librium" had been associated with excess mortality in the previous large U.S. CPSII study 21 .…”
Section: Results Had Many Similarities To Those Of Weich Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Another study failed to find a significant association, but had not been able to control for hypnotic dosage [2]. An analysis observing significant associations of hypnotic usage 5+/week with lung cancer and melanoma found that only melanoma remained significant after adjustment for confounders [3].…”
mentioning
confidence: 99%